Salespeople in the Surgical Suite: Relationships between Surgeons and Medical Device Representatives - Bonnie B. O’Connor; F Pollner; Adriane Fugh‐Berman (2016)
Industry payments to surgeons have received public attention, but little is known about the relationships between surgeons and medical device representatives. Medical device representatives ("device reps") have become an integral part of operating room personnel. The effect of their presence on patient care deserves discussion. We conducted a qualitative, ethnographic study to explore relationships between surgeons and medical device representatives, and characterize industry involvement in the training of surgeons. We used group and individual open-ended interviews to gain insight into the beliefs, values, and perspectives of surgeons and device reps. We conducted two focus groups, one with ear, nose, and throat surgeons, and one with hospital-based attending orthopedic surgeons. We also conducted individual interviews with three former or current medical device representatives, a director of a surgical residency program at an academic medical center, and a medical assistant for a multi-physician orthopedic practice. While surgeons view themselves as indisputably in charge, device reps work hard to make themselves unobtrusively indispensable in order to establish and maintain influence, and to imbue the products they provide with personalized services that foster a surgeon's loyalty to the reps and their companies. Surgeons view industry-funded training opportunities as a necessary service. Device reps and some surgeons believe that reps benefit patient care, by increasing efficiency and mitigating deficiencies among operating room personnel (including the surgeons themselves). Our study raises ethical questions about the reliance of surgeons on device reps and device companies for education and surgical assistance and practical concerns regarding existing levels of competence among OR personnel.